Comparison of mesophilic and thermophilic dark fermentation with nickel ferrite nanoparticles supplementation for biohydrogen production. (June 2021) - Zhang, Jishi; Zhao, Wenqian; Yang, Junwei; Li, Zhenmin; Zhang, Junchu; Zang, Lihua
Graphical abstract: Highlights: BioH2 production was enhanced by supplementing with NiFe2 O4 NPs. NiFe2 O4 NPs promoted mesophilic fermentation more than thermophilic process. Bacterial activity was improved by Fe and Ni ions from corrosion of NiFe2 O4 NPs. Clostridium butyricum were selectively enriched in the presence of NiFe2 O4 NPs. Butyrate-type fermentation dominated bioH2 production added with NiFe2 O4 NPs. Abstract: In this work, nickel ferrite nanoparticles (NiFe2 O4 NPs) was prepared to improve hydrogen (H2 ) production by dark fermentation. Moderate amounts (50–200 mg/L) promoted H2 generation, while excess NiFe2 O4 NPs (over 400 mg/L) lowered H2 productivity. The highest H2 yields of 222 and 130 mL/g glucose were obtained in the 100 mg/L (37 °C) and 200 mg/L NiFe2 O4 NPs (55 °C) groups, respectively, and the values were 38.6% and 28.3% higher than those in the control groups (37 °C and 55 °C). Soluble metabolites showed that NiFe2 O4 NPs enhanced the butyrate pathway, corresponding to the increased abundance of Clostridium butyricum in mesophilic fermentation. The endocytosis of NiFe2 O4 NPs indicated that the released iron and nickel favored ferredoxin and hydrogenase synthesis and activity and that NiFe2 O4 NPs could act as carriers in intracellular electron transfer. The NPs also optimized microbial community structure and increased the levels of extracellular polymeric substances, leading to increased H2 production.